Multicenter Study of Carbon-ion Radiotherapy for Oropharyngeal Non-squamous Cell Carcinoma - KANEKO, TAKASHI (In Vivo, 2021)
Background/Aim: To evaluate treatment outcomes of carbon-ion radiotherapy for oropharyngeal non-squamous cell carcinoma at four carbon-ion facilities in Japan. Patients and Methods: We retrospectively analyzed the cases of 33 patients with oropharyngeal non-squamous cell carcinoma who were treated with carbon-ion radiotherapy between November 2003 and December 2014. Results: The histology included adenoid cystic carcinoma (n=25) and mucosal malignant melanoma (n=4). No patients had T1 tumors; 23 had T4 tumors. The most-commonly prescribed dose was 57.6 Gy (RBE) in 16 fractions. The median follow-up period was 34.8 months (range=4.2-122.8 months). The 3-year local control and overall survival rates were 94.7% and 90.7%, respectively. There were no grade ≥4 acute adverse events. Only one patient experienced a grade ≥4 late adverse event. No patients experienced late adverse events related to swallowing or salivary function. Conclusion: Carbon-ion radiotherapy appears to be a promising treatment option for oropharyngeal non-squamous cell carcinoma.